Estudo comparativo de Dois irmãos e Cinzas do Norte, de Milton Hatoum, e A Selva, de Ferreira de Castro - Penalva, Gilson (2012)
The present study discusses processes of identification that take place in Brazilian Amazon and its literary representations from a comparative perspective, analyzing the novels A Selva, by the Portuguese writer Ferreira de Castro, and Dois Irmãos and Cinzas do Norte, by the Brazilian writer Milton Hatoum, focusing on hybridism and cultural difference, based on cultural and post-colonial theories. The idea is to point out, through a critical reading, the constructions developed by the two mentioned authors in respect to the discourses disseminated about that specific region. In the compared reading developed, it is possible to recognize at least two distinct projects (literary, social, discursive): one, giving priority to the interactions that take place along the several cultural exchanges there established, deconstructing representations historically understood as “true” in the region. Verifying the way such projects take part in the imaginary and symbolic construction of the Amazon region and culture is one of our main purposes.